Porous membrane electrode with catalysis and separation functions and preparation method and application thereof

By introducing conductive materials into the porous membrane to improve the conductivity and hydrophobicity, the problems of poor conductivity and unstable hydrophobic treatment in electrocatalytic nitric oxide reduction reaction are solved, and high-efficiency reduction and separation of ammonia are achieved, ensuring the porous membrane electrode Stability and reusability.

CN119265594APending Publication Date: 2025-01-07CENT SOUTH UNIV
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411331474.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-24
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

The existing porous membrane electrodes have poor conductivity and unstable hydrophobic treatment in electrocatalytic nitric oxide reduction reaction, resulting in water flooding problems and low ammonia separation efficiency of product.

Method used

By introducing conductive materials into the porous membrane, building a conductive skeleton, improving conductivity and hydrophobicity, and increasing the connectivity of the surface membrane skeleton, a porous membrane electrode with catalytic and separation functions is prepared for electrocatalytic nitric oxide reduction and synthesis of ammonia and Achieve in-situ separation of ammonia.

Benefits of technology

It has achieved efficient reduction of nitric oxide and stable separation of product ammonia, overcome the problems of poor conductivity and unstable hydrophobic treatment, and the porous membrane electrode structure is stable and reusable.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119265594A_ABST
    Figure CN119265594A_ABST
Patent Text Reader

Abstract

The invention discloses a porous membrane electrode with catalysis and separation functions and a preparation method and application thereof, and belongs to the technical field of electro-catalysis. The porous membrane electrode is formed by loading a catalytic material on the surface of a conductive porous membrane; the conductive porous membrane is formed by uniformly dispersing a conductive material in a hydrophobic resin porous membrane matrix. The preparation method of the porous membrane electrode comprises the following steps: uniformly mixing a conductive material, hydrophobic resin and an organic solvent to form a membrane preparation solution, performing membrane preparation on the membrane preparation solution to obtain a conductive porous membrane, and loading a catalytic material on the surface of the conductive porous membrane to obtain the porous membrane electrode. The porous membrane electrode is used for electro-catalytic reduction of nitric oxide, can efficiently reduce nitric oxide and realize in-situ separation of product ammonia, and is stable in operation.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a membrane electrode, in particular to a porous membrane electrode with catalytic and separation functions, and also to a preparation method of the porous membrane electrode, and its application in electrocatalytic conversion of nitric oxide into ammonia and efficient and stable separation of the product ammonia, belonging to the technical field of electrocatalytic reduction. Background Art

[0002] Nitrogen oxides are one of the main air pollutants, causing various environmental events such as acid rain, photochemical smog, and greenhouse effect, and can also seriously damage human health. At present, China has put forward strict requirements for the emission control of nitrogen oxides, and has successively promulgated industry emission standards such as GB31574-2015. Some provinces and cities have also formulated emission regulations that are more stringent than national standards, requiring that the emission concentration of nitrogen oxides in some key control areas shall not exceed 50mg / m 3 . The electrocatalytic reduction of nitric oxide can produce a series of nitrogen-containing products at room temperature and pressure, especially the product ammonia, which is an important industrial consumable and has economic benefits. In addition, the catalytic reduction of nitric oxide to synthesize ammonia is more environmentally friendly than the current industrial production of ammonia by the Haber-Bosch process (300-500°C, 100-200bar). In summary, the electrocatalytic reduction of nitric oxide to synthesize ammonia is a method for nitric oxide treatment and ammonia preparation with great application prospects.

[0003] The product ammonia after the electrocatalytic reduction of nitric oxide to synthesize ammonia enters the cathode electrolyte, and the subsequent separation means generally adopt methods such as stripping and alkali exchange, which are cumbersome and energy-intensive. Chinese patent CN 113789526B reports a hydrophobic material and a catalytic material loaded on its surface for separating ammonia produced in the electrocatalytic nitric oxide synthesis process, but the hydrophobic material used in this method is a hydrophobic treated porous metal material or a commercial porous membrane. The hydrophobic treatment of the porous metal material is unstable and easily causes problems such as flooding. The commercial porous membrane has poor conductivity and cannot adapt to more application scenarios. Summary of the invention

[0004] In view of the defects of the prior art, the first purpose of the present invention is to provide a porous membrane electrode with catalytic and separation functions, which builds a conductive skeleton inside the porous membrane by introducing a conductive material, thereby improving the conductivity of the porous membrane electrode and ensuring the hydrophobicity of the porous membrane electrode, thereby overcoming the technical problems such as unstable hydrophobic treatment of existing porous metal materials that easily causes flooding, and the poor conductivity of commercial porous membranes. In addition, the incorporation of conductive materials increases the connectivity between the surface membrane skeletons and improves the loading stability of metal-based catalytic materials.

[0005] The second object of the present invention is to provide a method for preparing a porous membrane electrode with catalytic and separation functions, which method is simple, low-cost and conducive to large-scale promotion and application.

[0006] The third object of the present invention is to provide an application of a porous membrane electrode with catalytic and separation functions, which is used for electrocatalytic reduction of nitric oxide to synthesize ammonia and realize in-situ separation of ammonia, so as to achieve the purpose of efficient reduction of nitric oxide and in-situ separation of product ammonia and stable operation, and the porous membrane electrode has a stable structure, can be reused, and can be promoted and applied.

[0007] In order to achieve the above technical objectives, the present invention provides a porous membrane electrode with catalytic and separation functions, which is composed of a catalytic material loaded on the surface of a conductive porous membrane; the conductive porous membrane is composed of a conductive material uniformly dispersed in a hydrophobic resin porous membrane matrix.

[0008] The present invention introduces conductive materials into the hydrophobic porous membrane to build a conductive skeleton inside the hydrophobic porous membrane, thereby improving the conductivity of the porous membrane electrode and increasing the connectivity between the surface membrane skeletons, providing a good supporting platform for the subsequent loading of metal-based catalytic materials. The introduction of conductive materials will not change the hydrophobicity of the porous membrane and the uniformity of the porous structure, and may even further improve the hydrophobicity, thereby enabling the porous membrane electrode to be directly used for electrochemical reduction and separation of soluble gaseous products.

[0009] As a preferred solution, the conductive material includes at least one of a conductive metal material, a conductive polymer material, a carbon material, and a conductive non-metal material. The conductive metal material is preferably at least one of copper, silver, aluminum, iron, gold, platinum, or palladium. The conductive polymer material is preferably at least one of polystyrene, polyethylene, polypropylene, polyaniline, and polythiophene. The carbon material is preferably at least one of graphite, carbon black, carbon nanotubes, graphene, and carbon fiber. The conductive non-metal material is preferably a conductive ceramic material.

[0010] As a preferred solution, the hydrophobic resin includes at least one of polytetrafluoroethylene, polyvinylidene fluoride, polypropylene, polyvinyl chloride, polysulfone, polyethersulfone, polyamide and polyimide.

[0011] As a preferred solution, the mass ratio of the conductive material to the hydrophobic resin in the conductive porous membrane is 1 to 5:10 to 15. If the amount of the conductive material is too low, the improvement of the conductivity of the porous membrane is limited. If the amount of the conductive material is too high, the film-forming properties of the porous membrane are affected. The mass ratio of the conductive material to the hydrophobic resin in the conductive porous membrane is further preferably 1 to 3:10.

[0012] As a preferred solution, the surface of the hydrophobic resin porous membrane substrate is provided with a conductive carbon layer, and the conductive carbon layer has a carbon content of 1 to 3 mg / cm2 Further forming a conductive carbon layer on the surface of the hydrophobic resin porous membrane substrate can significantly increase the surface resistance of the hydrophobic resin porous membrane substrate, and is also more conducive to the stable loading of the catalytic material.

[0013] As a preferred solution, the loading amount of the catalytic material on the surface of the conductive porous membrane is ≥ 2 mg / cm 2 , to ensure good catalytic performance.

[0014] As a preferred solution, the catalytic material is at least one of a metal element, a metal sulfide, a metal selenide, a metal phosphide, a metal nitride, and a boron-doped diamond; wherein the metal element in the metal element, the metal sulfide, the metal selenide, the metal phosphide, and the metal nitride is selected from at least one of lead, copper, cobalt, iron, nickel, gold, silver, platinum, or palladium. The metal element is preferably at least one of lead, copper, cobalt, iron, nickel, gold, silver, platinum, or palladium. The metal sulfide is preferably at least one of the sulfides of lead, copper, cobalt, iron, nickel, gold, silver, platinum, or palladium. The metal selenide is preferably at least one of the selenides of lead, copper, cobalt, iron, nickel, gold, silver, platinum, or palladium. The metal phosphide is preferably at least one of the phosphides of lead, copper, cobalt, iron, nickel, gold, silver, platinum, or palladium. The metal nitride is preferably at least one of the nitrides of lead, copper, cobalt, iron, nickel, gold, silver, platinum, or palladium. These catalytic materials are common catalytic materials in the art that have a catalytic effect on the electrochemical reduction of nitrogen monoxide.

[0015] The present invention also provides a method for preparing a porous membrane electrode with catalytic and separation functions. The method comprises mixing a conductive material, a hydrophobic resin and an organic solvent evenly to form a membrane-forming liquid, and the membrane-forming liquid is used to form a conductive porous membrane, and a catalytic material is loaded on the surface of the conductive porous membrane; or a conductive carbon layer is first sprayed on the surface of the conductive porous membrane, and then the catalytic material is loaded; thus, the electrode is obtained.

[0016] As a preferred solution, the mass proportion of the organic solvent in the membrane-forming solution is 80-90%.

[0017] As a preferred embodiment, the organic solvent includes at least one of alcohols, halogenated hydrocarbons, ketones, esters, and alicyclic hydrocarbons. Alcohols are preferably at least one of methanol, ethanol, isopropanol, n-butanol, isobutanol, and ethylene glycol. Halogenated hydrocarbons are preferably at least one of dichloromethane, chloroform, carbon tetrachloride, chlorobenzene, and o-dichlorobenzene. Ketones are preferably at least one of acetone, methyl butyl ketone, methyl ethyl ketone, and methyl isobutyl ketone. Esters are preferably at least one of methyl acetate, ethyl acetate, propyl acetate, and butyl acetate. Alicyclic hydrocarbons are preferably at least one of cyclohexane, cyclohexanone, and toluene cyclohexanone. Other polar solvents may also be selected, such as at least one of dimethyl sulfoxide (DMSO), N,N-dimethylformamide (DMF), N,N-dimethylacetamide (DMAc), and N-methylpyrrolidone (NMP).

[0018] As a preferred solution, the film is made by self-electrospinning, immersion phase transformation, and thermally induced phase separation. These methods are conventional wet film-making processes in the prior art, and can form porous membrane materials. The electrospinning method, for example, uses a film-making liquid as a slurry, the injection rate is 0.5-1.5 ml / h, the spinning voltage is set to 14-18 kV, the spinning distance is set to 10-15 cm, and the roller speed is 300-500 r / min. The immersion phase transformation method, for example, is to stir the film-making liquid evenly and then scrape it into a thin layer of 30-200 μm, and then solidify and separate it in deionized water. The thermally induced phase separation method, for example, is to stir the film-making liquid at 100-150 ° C until it is stable and uniform, then scrape it into a thin layer of 30-200 μm, and then solidify and separate it in deionized water.

[0019] As a preferred solution, the method of loading the catalytic material on the surface of the conductive porous membrane adopts self-drip coating, spray coating, electrodeposition, and gas phase physical deposition. These methods are conventional catalytic material loading methods in the prior art. For example, the drip coating method is as follows: after using Nafion117 solution as a binder and a catalyst to form a uniform slurry in anhydrous ethanol, it is gradually dripped on the surface of the porous membrane and heated to dry. For example, the spray coating method is as follows: after using Nafion117 solution as a binder and a catalyst to form a uniform slurry in anhydrous ethanol, a pressurized spray gun is used to evenly spray on the surface of the porous membrane and heat to dry. For example, the electrodeposition method is as follows: a porous membrane is used as a cathode, a platinum sheet is used as an anode, and an ionic solution of the catalyst is used as an electrolyte for constant current electrodeposition, and the current density is set to 5-30 mA / cm 2 The deposition time is 300 to 700 seconds. The gas phase physical deposition method is preferably selected from one of vacuum evaporation, sputtering coating and plasma coating, and the specific method parameters need to be determined according to the properties of the catalyst.

[0020] The present invention also provides an application of a porous membrane electrode with catalytic and separation functions, which is applied to electrocatalytic reduction of nitric oxide into ammonia and in-situ separation of ammonia. Electrocatalytic reduction of nitric oxide into ammonia and in-situ separation of ammonia process: cathode liquid and anode liquid are separated by a commercial proton membrane, the cathode liquid is a nitric oxide absorption liquid or a nitrite solution, the membrane electrode is a working electrode, the side of the membrane electrode loaded with a catalytic material faces the cathode liquid, and the other side faces the ammonia absorption chamber.

[0021] Compared with the prior art, the technical solution of the present invention has the following beneficial technical effects:

[0022] The porous membrane electrode provided by the present invention has good conductivity and hydrophobicity, as well as a stable and uniform porous structure, which can overcome technical problems such as unstable hydrophobic treatment of existing porous metal materials that easily causes flooding, and technical problems such as poor conductivity of commercial porous membranes.

[0023] The preparation method of the porous membrane electrode of the present invention is simple and low in cost, and is conducive to large-scale promotion and application.

[0024] The porous membrane electrode of the present invention is used for electrocatalytic reduction of nitric oxide to synthesize ammonia and realize in-situ separation of ammonia, which can achieve the purpose of efficient reduction of nitric oxide and in-situ separation of product ammonia and stable operation, and the porous membrane electrode has a stable structure, can be reused, and can be promoted and applied. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 This is a scanning electron microscope image of the CNT-doped PVDF membrane in Example 1, in which the mass ratio of carbon nanotubes: PVDF powder: DMF is 2.4:12:85.6.

[0026] Figure 2 This is a scanning electron microscope image of the undoped PVDF membrane in Example 2 with a PVDF powder:DMF mass ratio of 12:88.

[0027] Figure 3 This is a static contact angle diagram of the CNT-doped PVDF membrane in Example 1, in which the mass ratio of carbon nanotubes: PVDF powder: DMF is 2.4:12:85.6.

[0028] Figure 4 This is a static contact angle diagram of the undoped PVDF membrane in Example 2 with a PVDF powder:DMF mass ratio of 12:88.

[0029] Figure 5 It is a comparison of the static contact angles of the nanoCu / PVDF-C membrane electrode in Example 12 and the conductive carbon film after PTFE hydrophobic treatment in Example 13 before and after 4 hours of reaction.

[0030] in,

[0031] Figure 1 and Figure 2 The comparison shows that carbon nanotubes have a more complete membrane pore surface after doping, which can provide a good supporting platform for the subsequent loading of metal-based catalytic materials.

[0032] Figure 3 and Figure 4 The comparison shows that the incorporation of carbon nanotube materials does not basically change the hydrophobicity of the porous membrane. Figure 5 The changes in the static contact angles of the two materials before and after the reaction indicate that the carbon-doped PVDF membrane electrode has more stable hydrophobic properties than the conductive carbon membrane treated with PTFE hydrophobicity. DETAILED DESCRIPTION

[0033] The following embodiments and drawings are intended to further illustrate the content of the present invention, but are not intended to limit the scope of protection of the claims of the present invention.

[0034] Unless otherwise specified in the following examples, the chemical reagents used are conventional commercially available products and are analytically pure reagents.

[0035] The steps for preparing a conductive doped PVDF porous membrane by the immersion phase inversion method in the following embodiment are as follows: a conductive material, PVDF powder and an organic solvent are mixed in proportion, stirred at a constant temperature of 45°C for 6 hours and kept warm for 24 hours, and then formed by scraping with a 40-micron scraper. After that, phase solidification separation is performed with deionized water and the membrane is immersed in water for 72 hours, wherein the deionized water is replaced every 12 hours, and then the membrane is naturally air-dried in a fume hood to obtain a conductive doped PVDF porous membrane.

[0036] The steps for preparing a conductive doped PVDF porous membrane by electrospinning in the following embodiment are as follows: the conductive material powder, PVDF powder and DMF solvent are mixed in proportion, stirred at a constant temperature of 45°C for 6 hours and kept warm for 24 hours, and then the membrane-making liquid after standing is injected into the syringe of the electrospinning machine at an injection rate of 1.2 ml / h, the spinning voltage is set to 17 kV, the spinning distance is set to 15 cm, and the roller speed is 400 r / min.

[0037] The preparation method of nanoCu / PVDF-C membrane electrode in the following embodiment is as follows: using CNT as conductive doping material and N,N-dimethylformamide (DMF) as solvent, a carbon-doped PVDF membrane (PVDF-C) is prepared by immersion phase inversion method; on the surface of the cut dry carbon-doped PVDF membrane, 0.5 mg / cm 2 Conductive carbon black was sprayed to increase the friction between the materials, and then a nano copper powder solution with Nafion binder (Nafion content was 5 μL / mg nano Cu) was sprayed, with a loading of 2 mg / cm 2 .

[0038] The preparation method of the CuNi / PVDF-C membrane electrode in the following embodiment is as follows: using CNT as a conductive doping material and N,N-dimethylformamide (DMF) as a solvent, a carbon-doped PVDF membrane (PVDF-C) is prepared by an immersion phase inversion method; nano-carbon powder and Nafion dispersion are ultrasonically dispersed in anhydrous ethanol in a certain proportion, and are sprayed on the surface of the PVDF-C membrane by pressure, and then dried; a CuNi catalyst is electrodeposited on the surface of the PVDF-C membrane by a three-electrode system constant current mode, and an electrodeposition electrolyte (CuNi) is prepared by copper sulfate, nickel sulfate and trisodium citrate. 2+ :Ni 2+ :cit=2:8:1.5), PVDF-C membrane was used as working electrode, platinum sheet was used as counter electrode, Hg / Hg2SO4 was used as reference electrode, and Luggin capillary was used to prevent contamination of reference electrode, and reduction current was selected as 20mA / cm 2 , the deposition time is 500s.

[0039] The electrocatalytic reduction of nitrogen monoxide to prepare ammonia in the following examples uses a three-electrode system for electrocatalytic reaction. The cathode chamber and the anode chamber of the three-electrode system are separated by a DuPont N117 proton membrane, and the membrane electrode separates the cathode part into a cathode chamber and an ammonia absorption chamber. The cathode chamber electrolyte is a sodium sulfate solution (concentration of 0.1M) and argon is introduced to remove dissolved oxygen and then NO is introduced to saturate its concentration. The anode chamber electrolyte is a potassium hydroxide solution (concentration of 1M), the membrane electrode is used as a working electrode, the platinum sheet is used as a counter electrode, the Ag / AgCl electrode is used as a reference electrode, and the reduction voltage is selected as -1.27V (vs Ag / AgCl).

[0040] The porosity of the membrane in the following examples is measured by the weight method, which is to immerse the sample in isopropanol for 30 minutes to fully wet the membrane pores, and then measure the weight of the saturated wetted membrane and the dry membrane respectively. The porosity ε of the membrane can be calculated by the following formula:

[0041]

[0042] Where w1 is the weight of the wet film, w2 is the weight of the dry film, and ρ i is the density of isopropanol, ρ p is the polymer density.

[0043] Example 1

[0044] Using carbon nanotubes as conductive doping materials, N,N dimethylformamide (DMF) as solvent, and preparing the membrane liquid carbon nanotubes: PVDF powder: DMF mass ratio of 2.4:12:85.6, the PVDF-C porous membrane was prepared by immersion phase inversion method, and the coating thickness was 35 microns. The porosity of the prepared porous membrane was measured by weight method, which was 70.1%, the resistance was 96MΩ, and the surface was sprayed with 2mg / cm 2The resistance after carbon black is 0.02MΩ. The scanning electron microscope image of the carbon-doped PVDF porous membrane prepared in Example 1 is as follows: Figure 1 The static contact angle of the carbon-doped PVDF porous membrane prepared in Example 1 is shown in Figure 3 shown.

[0045] Example 2 (Comparative Example)

[0046] Using DMF as solvent, the mass ratio of PVDF powder to DMF was 12:88, and the PVDF-C porous membrane was prepared by immersion phase inversion method with a coating thickness of 35 microns. The porosity of the prepared membrane was measured by weight method and was 76.7%, the resistance was >200MΩ, and the surface was sprayed with 2mg / cm 2 The resistance after carbon black is still>200MΩ. The scanning electron microscope image of the carbon-doped PVDF porous membrane prepared in Example 2 is as follows: Figure 2 The static contact angle of the carbon-doped PVDF porous membrane prepared in Example 2 is as shown in Figure 4 shown.

[0047] Example 3 (Comparative Example)

[0048] Using carbon nanotubes as conductive doping materials, N,N dimethylformamide (DMF) as solvent, and preparing the membrane liquid carbon nanotubes: PVDF powder: DMF mass ratio of 4.8:12:83.2, the PVDF-C porous membrane was prepared by immersion phase inversion method, and the coating thickness was 35 microns. The obtained membrane was not tough enough and was broken by airflow during the ventilation process.

[0049] Example 4

[0050] Commercial nano copper powder was used as the conductive doping material, N,N dimethylformamide (DMF) was used as the solvent, and the membrane preparation liquid was prepared with a mass ratio of nano copper powder: PVDF powder: DMF of 2.4:12:85.6. The PVDF-C porous membrane was prepared by immersion phase inversion method, and the coating thickness was 35 microns. The porosity of the prepared PVDF-nano Cu porous membrane was measured by weight method to be 71.5%, the resistance was 101MΩ, and the surface was sprayed with 2mg / cm 2 The resistance after carbon black is 0.03MΩ.

[0051] Example 5

[0052] Using carbon nanotubes as conductive doping materials, N,N dimethylformamide (DMF) as solvent, and preparing the membrane liquid carbon nanotubes: PVDF powder: DMF mass ratio of 0.5:12:87.5, the PVDF-C porous membrane was prepared by immersion phase inversion method, and the coating thickness was 35 microns. The porosity of the prepared membrane was measured by weight method, which was 71.1%, the resistance was 194MΩ, and the surface was sprayed with 2mg / cm 2 The resistance after carbon black is 0.5MΩ.

[0053] Example 6

[0054] Using carbon nanotubes as conductive doping materials, N,N-dimethylformamide (DMF) as solvent, and preparing the membrane liquid carbon nanotubes: PVDF powder: DMF mass ratio of 2.4:12:85.6, PVDF-C porous membrane was prepared by electrospinning. The porosity of the prepared membrane was measured by weight method, and the resistance was 73.6%, 100MΩ, and the surface was sprayed with 2mg / cm 2 The resistance after carbon black is 0.04MΩ.

[0055] Example 7

[0056] The nano Cu / PVDF-C membrane electrode was prepared by using the immersion phase conversion method with a mass ratio of carbon nanotubes: PVDF powder: DMF of 2.4:12:85.6. The three-electrode system was used to electrocatalyze the reduction of nitric oxide to synthesize ammonia, and the reaction current was 11.05 mA / cm 2 , the Faraday efficiency of ammonia is 73% and the ammonia separation rate is 97%.

[0057] Example 8

[0058] The nano Cu / PVDF-C membrane electrode was prepared by porous membrane preparation and immersion phase conversion method using a carbon nanotube: PVDF powder: DMF mass ratio of 1.2:12:86.8. The three-electrode system was used to electrocatalyze the reduction of nitric oxide to synthesize ammonia, and the reaction current was 6.87 mA / cm 2 , the Faradaic efficiency of ammonia is 63% and the ammonia separation rate is 95%.

[0059] Example 9

[0060] The CuNi / PVDF-C membrane electrode was prepared by using the immersion phase conversion method with a mass ratio of carbon nanotubes: PVDF powder: DMF of 2.4:12:85.6. The three-electrode system was used to electrocatalyze the reduction of nitric oxide to synthesize ammonia, and the reaction current was 22.25 mA / cm 2 , the Faraday efficiency of ammonia is 90% and the ammonia separation rate is 95%.

[0061] Example 10

[0062] The CuNi / PVDF-C membrane electrode was prepared by using the immersion phase conversion method with a mass ratio of carbon nanotubes: PVDF powder: DMF of 3:12:85.6. The three-electrode system was used to electrocatalyze the reduction of nitric oxide to synthesize ammonia, and the reaction current was 31.26 mA / cm 2 , the Faraday efficiency of ammonia is 91% and the ammonia separation rate is 94%.

[0063] Embodiment 11

[0064] The nano Cu / PVDF-C membrane electrode was prepared by using a nano copper powder: PVDF powder: DMF mass ratio of 2.4:12:85.6 and an immersion phase conversion method. The three-electrode system was used to electrocatalyze the reduction of nitric oxide to synthesize ammonia, and the reaction current was 10.59 mA / cm 2 , the Faraday efficiency of ammonia is 80% and the ammonia separation rate is 96%.

[0065] Example 12

[0066] The nano Cu / PVDF-C membrane electrode was prepared by using the immersion phase conversion method with a mass ratio of nano copper powder: PVDF powder: DMF of 2.4:12:85.6. The three-electrode system was used to carry out the electrocatalytic nitric oxide reduction reaction for ammonia synthesis. The electrolysis was continued for 4 hours, and the static contact angles before and after the test were as follows: Figure 5 shown.

[0067] Example 13 (Comparative Example)

[0068] The commercial porous carbon cloth was treated with hydrophobicity. The dried commercial porous carbon cloth was soaked in a concentrated polytetrafluoroethylene dispersion (60 wt%) for 2 min, then dried statically, and sprayed with a nano copper powder solution with a Nafion binder (Nafion content of 5 μL / mg nano Cu) with a loading of 2 mg / cm 2 The three-electrode system was used to carry out the electrocatalytic nitric oxide reduction reaction to synthesize ammonia. The electrolysis lasted for 4 hours. The static contact angles before and after the test were as follows: Figure 5 shown.

Claims

1. A porous membrane electrode with catalytic and separation functions, characterized in that: The catalyst material is loaded on the surface of a conductive porous membrane; the conductive porous membrane is composed of conductive materials uniformly dispersed in a hydrophobic resin porous membrane matrix.

2. The porous membrane electrode with catalytic and separation functions according to claim 1, characterized in that: The conductive material includes at least one of a conductive metal material, a conductive polymer material, a carbon material, and a conductive non-metal material.

3. The porous membrane electrode with catalytic and separation functions according to claim 1, characterized in that: The hydrophobic resin includes at least one of polytetrafluoroethylene, polyvinylidene fluoride, polypropylene, polyvinyl chloride, polysulfone, polyethersulfone, polyamide and polyimide.

4. A porous membrane electrode with catalytic and separation functions according to any one of claims 1 to 3, characterized in that: The mass ratio of the conductive material to the hydrophobic resin in the conductive porous membrane is 1-5:10-15.

5. The porous membrane electrode with catalytic and separation functions according to claim 1, characterized in that: The surface of the hydrophobic resin porous membrane substrate is provided with a conductive carbon layer, and the conductive carbon layer has a carbon content of 1 to 3 mg / cm 2 The loading amount of the catalytic material on the surface of the conductive porous membrane is ≥2 mg / cm 2 .

6. A porous membrane electrode with catalytic and separation functions according to claim 1 or 5, characterized in that: The catalytic material is at least one of a metal element, a metal sulfide, a metal selenide, a metal phosphide, a metal nitride, and boron-doped diamond; wherein the metal element in the metal element, the metal sulfide, the metal selenide, the metal phosphide, and the metal nitride is selected from at least one of lead, copper, cobalt, iron, nickel, gold, silver, platinum, or palladium.

7. The method for preparing a porous membrane electrode having catalytic and separation functions according to any one of claims 1 to 6, characterized in that: A conductive material, a hydrophobic resin and an organic solvent are uniformly mixed to form a membrane-forming solution, the membrane-forming solution is used to form a conductive porous membrane, and a catalytic material is loaded on the surface of the conductive porous membrane; or Firstly, a conductive carbon layer is sprayed on the surface of the conductive porous membrane, and then a catalytic material is loaded; thus, the membrane is obtained.

8. The method for preparing a porous membrane electrode having catalytic and separation functions according to claim 7, characterized in that: The mass proportion of the organic solvent in the membrane-making solution is 80-90%; The organic solvent includes at least one of alcohols, halogenated hydrocarbons, ketones, esters, and alicyclic hydrocarbons.

9. The method for preparing a porous membrane electrode having catalytic and separation functions according to claim 7, characterized in that: The membrane is prepared by self-electrospinning, immersion phase conversion, thermally induced phase separation or blade coating.

10. The use of a porous membrane electrode with catalytic and separation functions as claimed in claim 6, characterized in that: It is applied to the electrocatalytic reduction of nitric oxide into ammonia and the simultaneous in-situ separation of ammonia.

Citation Information

Patent Citations

  • A method for preparing ammonia by electrochemical reduction of nitric oxide

    CN113789526B